Hobson-Jobson : A Glossary of Colloquial Anglo-Indian Words and Phrases, and of Kindred Terms, Etymological, Historical, Geographical, and Discursive - Yule, Henry, (Brill | Manohar Publishers & Distributors, 2024)
Languages do not see barriers, and they adopt certain words while traversing to distant lands. Indian lexicons in English came to prominence, when the Portuguese, Dutch, and other colonial nations before the British Raj learned about specific Indian vocabularies and adopted them into their dictionaries. Many itinerary literature in the form of travelogues, botanical, medical, and miscellaneous works coming from the said countries had left their account and they have written certain terms and terminologies, which did not have an equivalent in European languages. Also, with the establishment of the Asiatic Society of Bengal and the reports, diaries, and accounts written by the British orientalists, government officials, and linguists, many Indian lexicons came into being from their compositions. This eventually led to the formation of Anglo-Indian words. Hobson Jobson is the corruption of the slogan Shia Muslim British-Indian soldiers during the Muharram, which is 'Ya Hasan Ya Hussain!'. This dictionary contains more than a thousand Anglo-Indian terms and was written by Henry Yule and A.C. Burnell, with additions made by William Crooke in 1903.